Criminological Analysis of The Crime of Murder Female College Students in Pandeglang Conducted by Ex-Girlfriend Using the Toilet - Rahmawati; Kezia Hera Putri; Adila Fitriani; Asmak Ul Hosnah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
This journal discusses the crime of murder, particularly in the context of femicide in Indonesia. A murder case occurred in Pandeglang Regency, where Elisa, a 22-year-old university student, was murdered by her ex-boyfriend, Riko. Riko felt hurt and jealous after finding out Elisa had a new lover, so he was obsessed with getting back together with Elisa. This act is an example of femicide, a gender-based violence that often occurs in Indonesia. This research uses a combined theory of criminal acts and empirical legal research methods. The results of this study explain that femicide is one of the causes of the crime of murder against young women. The purpose of this research is to understand the application of the law to the crime of murder and how the judge decided on the sanctions against the perpetrator, in accordance with the Criminal Code.